Management Strategies in Pericardial Emergencies - Seferović, Petar M.; Ristić, Arsen D.; Imazio, Massimo; Maksimović, Ružica; Simeunović, Dejan; Trinchero, Rita; Pankuweit, Sabine; Maisch, Bernhard (Herz, 2006)
The most frequent pericardial emergency is cardiac tamponade, but complications of an acute coronary syndrome and aortic dissection may also involve the pericardium. Acute pericarditis can also represent a medical emergency due to chest pain of upsetting intensity. Decompensations in chronic advanced constriction and in the clinical course of purulent pericarditis necessitate critical care as well. The diagnosis of cardiac tamponade is based on clinical presentation and physical findings, confirmed by echocardiography and cardiac catheterization. Tamponade is an absolute indication for urgent drainage, either by pericardiocentesis or surgical pericardiotomy. The approach for pericardiocentesis can be subxiphoid or intercostal using echocardiographic or fluoroscopic guidance. Urgent drainage, combined with intravenous antibiotics, is also mandatory in suspected purulent pericarditis. If confirmed, it should be combined with intrapericardial rinsing (best by a surgical drainage). Pericardiocentesis is contraindicated in cardiac tamponade complicating aortic dissection. This condition should immediately lead to cardiac surgery. Although pericardiectomy is the only treatment for permanent constriction, this procedure is contraindicated when extensive myocardial fibrosis and/or atrophy are demonstrated. Iatrogenic tamponade may occur during percutaneous mitral valvuloplasty, implantation of pacemakers, electrophysiology and radiofrequency ablation procedures, right ventricular endomyocardial biopsy, percutaneous coronary interventions, and rarely during Swan-Ganz catheterization. The authors report on a 79-year-old who suffered coronary perforation and cardiac tamponade during elective stent implantation. Tamponade was successfully treated with pericardiocentesis and implantation of a membrane-covered graft stent. Subsequent recurrent pericarditis/postpericardial injury syndrome with moderate pericardial effusion was initially treated with aspirin and then with aspirin and colchicine. At 6 months, the patient is in stable remission even after withdrawal of colchicine. Natural history of pericardial diseases can be complicated with pericardial emergencies requiring prompt diagnosis, intensive care with hemodynamic monitoring, and early aggressive management. Medical supportive measures, drainage of pericardial effusion, surgical pericardiotomy, and pericardiectomy should be applied when needed with no delay. This procedural approach also applies to iatrogenic interventions leading to tamponade.